Analisis Persepsi ASN terhadap Kebijakan Pemotongan Zakat Profesi dalam Meningkatkan Penghimpunan Zakat (Studi Kasus di Badan Amil Zakat Nasional Kabupaten Brebes) - Firda Zahrotul Millah; Sabila Azmi Usamah; Dewi Setyowati; Mahardhika Cipta Raharja (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the implementation of the professional zakat deduction policy for State Civil Apparatus (ASN) and examine ASN's views on the policy in increasing zakat collection at the National Zakat Agency (BAZNAS) of Brebes Regency. The background of this study is based on the failure to achieve optimal realization of zakat potential despite the automatic zakat deduction policy being implemented. This study applies a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, observation, and documentation involving BAZNAS managers and ASN as key informants. The results revealed that the policy has been implemented administratively through direct deductions from ASN salaries, but still faced obstacles related to limited socialization, lack of transparency, and varying levels of ASN trust in zakat management institutions. ASN's views on this policy tend to be positive although they are still influenced by factors of understanding, economic conditions, and levels of trust in zakat management institutions. This policy has made a positive contribution to increasing zakat collection, although it has not yet reached its maximum potential.